The Development of Teaching Aids with Green Chemistry as A Learning Media for Thermochemical Materials - Annur, Hijroh Rosiatun; Wardani, Sri; Sumarni, Woro (Universitas Negeri Semarang, 2021)
This development research aimd to: (1) Develop simple thermochemical teaching aids (2) Practical activities with the concept of Green chemistry that were environmentally friendly and safe to use (3) Obtain teacher responses to thermochemical teaching aids with Green chemistry as an alternative to the limited pre-practicum facilities. The development model used in this research was the 4-D model by Thiagarajan, Semmel, and Semmel which had been modified from four stages to three stages, namely: (1) Define (2) Design and (3) Develop (development). The stages carried out include (1) preliminary studies (2) product development and (3) product testing. The results of the preliminary study indicated that the development of teaching aids as a substitute for practicum activities was needed due to the limited existing facilities and infrastructure. Also, because thermochemical material had a high level of understanding and the abstractness of the concept, it was necessary to carry out practicum activities. The use and development of calorimetry props was an alternative in the implementation of thermochemical material practicum activities and by utilizing waste, it was possible to present simple calorimetry props that were environmentally friendly and safe to use. The results of product development in the form of props obtained the validity of the material with the results of 0.89 and the validity of the media with the results of 0.90, therefore the validation results of the props were categorized as valid. The practicality of the teaching aids was Green chemistry 88%, the result shows that the teaching aids developed were very practical so that these props were suitable for practicum. While the results of the teacher's response to the teaching aids with an overall average of 3.75 (maximum score of 4), based on these results indicate that the overall response of students to the teaching aids was very good.